Understanding the strategies to attain the best performance of all inorganic lead‐free perovskite solar cells: Theoretical insights. (1st July 2022) - Roy, Priyanka; Khare, Ayush
Summary: Within a decade of their existence, the potential of Perovskite solar cells (PSCs) has been recognized by the research community. To date, the highest power conversion efficiency (PCE) attained by PSCs has touched the 25.8% mark. However, most of the leading PSCs have incorporation of toxic lead (Pb), posing a barrier on the market acceptability of these cells. Inorganic lead‐free PSCs are being explored extensively as clean and green energy sources. By bridging the performance gap and stability issues, the drawbacks of lead‐free PSCs can be minimized. In this work, we have optimized CsSn0.5 Ge0.5 I3 ‐based PSCs using various organic and inorganic transport layers. A comparative analysis of all the simulated cells in terms of capacitance‐voltage (C‐V) and conductance‐voltage (G‐V) characterization has been done. This work reveals the decisive role of charge transport layers (CTLs) in the determination of the built‐in potential of the cell. The impact of absorber layer thickness (with different levels of defect densities), variation of thickness of electron transport layer (ETL), and hole transport layer (HTL) on the performance of PSCs is studied. The results of study on the effect of carrier concentration on the absorber layer, ETL, and HTL (using both organic and inorganic charge transport layers) on the performance of the cell is also conducted. This study explains the role of energy band level tuning required between CTLs and the absorber layer. The role of band offset at the interface of the CTL (ETL/HTL) and perovskite layer upon charge transportation and collection mechanisms are explained in detail. We have calculated and explained the optimum Valence Band Offset and Conduction Band Offset required for a PSC to exhibit the best possible performance. In addition, we have analyzed the role of contact formation and optimum barrier height (¢B ) required between HTL and back contact to obtain efficient PSC using different back contacts. Upon using similar cell configuration and different back contacts (Ni, Au, and Ag), the optimized values of (VBO, ¢B ) are (0.15 eV, −0.05 eV), (0.1 eV, −0.4 eV), and (−0.15 eV, −0.51 eV), respectively. Abstract : Charge carrier collection and extraction mechanism at different valance band and conduction band offset levels performed and criteria to obtain best performance has been explained. Barrier height calculation at varioius VBO levels using different cathodes are done. C–V and G–V characterization of the PSCs has been studied and optimiozation of PSC to attain the best possible performance has been conducted.